2017
DOI: 10.2147/dddt.s124034
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence study of a new sildenafil 100 mg orodispersible film compared to the conventional film-coated 100 mg tablet administered to healthy male volunteers

Abstract: A new orodispersible film formulation of the phosphodiesterase type 5 inhibitor, sildenafil, has been developed to examine the advantages of an orally disintegrating film formulation and provide an alternative to the current marketed products for the treatment of erectile dysfunction. The pharmacokinetics of the sildenafil 100 mg orodispersible film (IBSA) was compared to that of the conventional marketed 100 mg film-coated tablet (Viagra®) after single-dose administration to 53 healthy male volunteers (aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 22 publications
3
39
0
Order By: Relevance
“…We performed rectal administration of sildenafil ODF formulation, which is rapidly absorbed in the mucous membranes [ 12 ]. Some studies have reported rectal administration of medication as an alternative route for dogs that are not able to receive medication orally because of seizure [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed rectal administration of sildenafil ODF formulation, which is rapidly absorbed in the mucous membranes [ 12 ]. Some studies have reported rectal administration of medication as an alternative route for dogs that are not able to receive medication orally because of seizure [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orodispersible tablets 83 ODT present similar in appearance to conventional tablets, the rapid penetration of water through capillary 84 action into the porous framework leads to disintegration in the 30 s -3 min range [5,6]. The main 85 production strategies include lyophilisation, moulding or direct compression using peculiar excipients.…”
mentioning
confidence: 99%
“…It was found that the sildenafil ODF was bioequivalent to that of the conventional tablet (Viagra ® ). The plasma concentration-time profiles of sildenafil and the metabolite were nearly superimposable between the two dosage forms (Radicioni et al, 2017). However, after sublingual or buccal administration of the ropinirole ODF, a fast absorption was achieved within 15 min.…”
Section: Discussionmentioning
confidence: 90%